High-temperature challenges: electrochemical investigations into molten salt corrosion mechanisms - Yu, Fuzhen; Nicholls, John R.; Aria, Adrianus Indrat; Syed, Adnan U. (MDPI, 2026)
Thermal energy storage (TES) systems are widely employed in concentrated solar power (CSP) applications as a means of storing and dispatching energy. Typical thermal fluids used in TES systems include molten salts, such as solar salt (a KNO3–NaNO3 eutectic), as well as other inorganic salts currently under consideration. While these molten nitrate, chloride, sulfate, and carbonate salts offer favourable thermal properties, they can induce significant corrosion of metallic containment materials, leading to reduced system efficiency and component lifetime. Despite extensive post-exposure studies, in situ electrochemical understanding of corrosion mechanisms in molten solar salt remains limited, particularly for emerging alloys such as FeCrAl. In this study, the in situ corrosion behaviour of structural alloys in molten solar salt was investigated using electrochemical impedance spectroscopy (EIS). Complementary post-exposure characterization was performed using destructive techniques, including scanning electron microscopy (SEM) and energy-dispersive X-ray spectroscopy (EDX), to assess microstructural and chemical changes. The materials evaluated were stainless steel SS316 and comparatively underexplored Kanthal FeCrAl alloys, exposed to molten solar salt (40 wt% KNO3–60 wt% NaNO3) at 545 °C. The electrochemical and microstructural analyses indicate that FeCrAl exhibits superior corrosion resistance associated with the formation of a more stable and protective oxide scale, compared to SS316 under the investigated conditions. This study provides new electrochemical evidence supporting the suitability of FeCrAl alloys for TES applications, while also indicating that SS316 may develop improved corrosion resistance over extended exposure durations, highlighting the importance of long-term performance assessment.
This article belongs to the Special Issue Alloy Materials Degradation and Microstructural Study
Keywords: concentrating solar power (CSP); thermal energy storage (TES); molten salt corrosion; electrochemical characterization; solar salt; 34 Chemical Sciences; 7 Affordable and Clean Energy; 3402 Inorganic chemistry